Resolvin D1 suppresses inflammation‐associated tumorigenesis in the colon by inhibiting IL‐6‐induced mitotic spindle abnormality. Issue 5 (1st April 2021) - Lee, Ha‐Na; Choi, Yeon‐Seo; Kim, Seong Hoon; Zhong, Xiancai; Kim, Wonki; Park, Joon Sung; Saeidi, Soma; Han, Byung Woo; Kim, Nayoung; Lee, Hye Seung; Choi, Yoon Jin; Baek, Jeong‐Heum; et al.
Abstract: While failure in resolution of inflammation is considered to increase the risk of tumorigenesis, there is paucity of experimental as well as clinical evidence supporting this association. Resolvin D1 (RvD1) is a representative pro‐resolving lipid mediator that is endogenously generated from docosahexaenoic acid for the resolution of inflammation. Here, we report a decreased level of RvD1 in the blood from colorectal cancer patients and mice having inflammation‐induced colon cancer, suggesting plasma RvD1 as a potential biomarker for monitoring colorectal cancer. Administration of RvD1 attenuated dextran sodium sulfate (DSS)‐induced colitis and azoxymethane (AOM) plus DSS‐induced colorectal carcinogenesis by suppressing the production of interleukin‐6 (IL‐6) and IL‐6‐mediated chromosomal instability. The protective effect of RvD1 against chromosomal instability is associated with downregulation of IL‐6‐induced Cyclin D1 expression, which appears to be mediated by blocking the Janus kinase 2 (JAK2)‐signal transducer and activator of transcription 3 (STAT3) axis. RvD1 inhibited the STAT3 signaling pathway by interfering with the binding of IL‐6 to its receptor (IL‐6R), suggesting the novel function of RvD1 as a putative IL‐6R antagonist. Together, our findings suggest that RvD1‐mediated blockade of IL‐6 signal transmission may contribute to inhibition of chromosomal instability and tumorigenesis.